Pengelolaan Sekolah Ramah Anak (SRA) Berbasis Pendekatan Deep Learning (DL) di KB Az Zahwa, Trenggalek, Indonesia - Reni Sulistina Sulistina; Nasima Wuri Wardani (Universitas Islam Lamongan, 2025)
This study analyzes the strategies, implementation, and challenges of managing a Child Friendly School (CFS) based on the Deep Learning (DL) approach in early childhood education. The research was motivated by the low level of CFS implementation in Indonesian early childhood institutions and the need to integrate pedagogical principles that promote mindful, meaningful, and enjoyable learning to create a safe, inclusive, and participatory environment. A qualitative case study was conducted at Play Group Az Zahwa Trenggalek. Data were collected through semi- structured interviews, observations, documentation, and focus group discussions, and analyzed using data reduction, thematic analysis, and triangulation. The findings reveal that DL based CFS management is implemented through three stages: preparation, planning, and monitoring/evaluation. Preparation emphasizes strengthening school–parent partnerships, while planning involves developing lesson plans that integrate DL principles into play-based activities. Monitoring and evaluation are conducted through regular supervision and inclusive policies. The implementation of DL enhances children’s focus, engagement, and motivation through exploratory and reflective learning experiences. However, challenges include limited facilities, teachers’ digital literacy gaps, academically oriented parental expectations, and weak institutional policies. The study concludes that integrating CFS and DL supports holistic and humanistic management model in early childhood education.